Outcome Analysis Among Meningioma Genomic Subgroups Identifies Decreased Recurrence Free Survival in PI3K Activated Tumors. (1st September 2019) - Youngblood, Mark W; Sheth, Amar; Zhao, Amy; Montejo, Julio D; Duran, Daniel; Li, Chang; Tyrtova, Evgeniya; Ozduman, Koray; Miyagishima, Danielle F; Boetto, Julien; Peyre, Matthieu; Omay, Sacit Bulent; et al.
Abstract: INTRODUCTION: Previous studies have established relationships between meningioma molecular features and clinical outcome, including deoxyribonucleic acid (DNA)-methylation patterns, TERT promoter mutations, and various chromosomal copy number changes. These relationships stratify patients according to risk of recurrence and progression, thereby guiding difficult postoperative decisions regarding adjuvant therapies and frequency of follow-up. However, the associations of somatic driver mutations with prognosis is relatively less explored, and may yield actionable insights regarding meningioma pathogenesis and patient management. METHODS: Available outcome-related data for over 450 meningiomas was collected from retrospective chart review, including extent-of-resection, postoperative therapy, radiological recurrence, long-term clinical events, and Karnofsky performance score. All samples underwent targeted and/or whole-exome sequencing followed by independent classification based on (i) driver mutation and (ii) COSMIC mutational signature. Statistical relationships were investigated between genomic and patient outcome variables using Fisher's exact tests, Kaplan-Meier curves, and Cox proportional hazards modeling. RESULTS: We found that KLF4 meningiomas were more likely to illicit long-term symptoms in patients, while POLR2A tumors exhibited the highest average number of years until recurrence. Significant relationships were not identified between mutational signature and outcome. At 5 yr, we observed divergence in recurrence-free survival (RFS) between PI3K activated (AKT1 or PIK3CA mutant) and non-PI3K grade 1 meningiomas. Multivariable Cox proportional hazards analysis confirmed PI3K mutants as an independent significant predictor of RFS from grade, gender, Ki-67, and other established features. CONCLUSION: Patients with KLF4-mutant meningiomas, which typically occur in the skull base and with elevated edema, may experience increased incidence of long-term symptoms. Meningiomas harboring activating PI3K mutations exhibit decreased progression free survival, suggesting they could benefit from closer radiologic monitoring or adjuvant therapies. Our results further validate the utility of genomic profiling in meningioma patients, and suggest the need for multimodal molecular integration for optimal prognostic stratification.